Teaching Children to Programming on the Example of the Scratch Program - Tilavoldiyev Azizbek Otabek ogli; Xolmatov Abrorjon Alisher ogli; Hoshimov Bahodirjon Muminjonovich; Uzokov Barhayot Muhammadiyevich (Genius Publishing Group, 2022)
This article is devoted to teaching children programming using the Scratch program as an example. Like a human, a computer communicates in its own language. It is a computer-only language that has limited vocabulary and strict spelling rules. A "language" that a computer understands and communicates with is called a programming language. Anyone who knows any programming language can easily create their own program
Keywords: communicates; program; programming; rules